PERANAN LEMBAGA PERLINDUNGAN HAK CIPTA DI INDONESIA DALAM MEMBANTU PENEGAKAN HUKUM HAK CIPTA - Adryan Rizky Pratama; Hernawan Hadi (Fakultas Hukum Universitas Sebelas Maret, 2025)
This article aims to examine the role of copyright protection institutions in Indonesia, regarding the relevance of law enforcement and legal protection that applies to a musical copyrighted work. The method used in this research is normative (legal research). This legal writing uses a statute approach by reviewing the latest legislation that is still effect until now as the legal basis for copyright, namely Law Number 28 of 2014 in depth the content inside the law it. Copyright as a personal ownership rights to a work that was born due to human intellectual abilities really needs to be enforced, there is very little public awareness about copyright law, one of which is caused by the minim of knowledge of the community who underestimates the cpyright issUndang-Undange, therefore efforts are needed from law enforcement and institutions that regulate in more detail about copyright law, this is very needed as a means of distribution to creators of work or creators or copyright holders. Given the relevance of copyright law in Inodonesia which not yet strong enough to regulate violations of the law as well as the effectiveness of the distrubution of economic rights and moral rights that should be distributed to creators, further researche is needed to find out how the existence of copyright law in the digitalization era in Indonesia and further study of the problems that occur today are needed. The result of research and studies show the enforcement of copyright law that is sought by LMKN includes outreach to the public as well as what the agency does the law enforcement parties to further strengthen the effectiveness of copyright law, and reduce the occurence of piracy of works which still very common in Indonesia until now.